2019
DOI: 10.1149/2.0151907jes
|View full text |Cite
|
Sign up to set email alerts
|

Nanofiber Fuel Cell MEAs with a PtCo/C Cathode

Abstract: PtCo/C and Pt/C catalyst powders were incorporated into electrospun nanofiber and conventional sprayed cathode membraneelectrode-assemblies (MEAs) at a fixed electrode loading of 0.1 mg Pt /cm 2 . The binder for PtCo/C nanofiber cathodes and Pt/C nanofiber anodes was a mixture of Nafion and poly(acrylic acid) (PAA), whereas the sprayed electrode MEAs utilized a neat Nafion binder. The structure of electrospun fibers was analyzed by scanning transmission electron microscopy (STEM) and energy-dispersive X-ray sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 32 publications
0
36
0
Order By: Relevance
“…Several state‐of‐the‐art catalytic systems have approached similar HCD performance (including credible but not printed results as compiled in Figure S18, Supporting Information). The strategies of Pt‐ionomer relative distribution tuning with carbon support modification [ 43,68,69 ] and agglomerate engineering [ 70 ] have shown promises in enhancing both LCD and HCD performance. Catalytic activity is less relevant to HCD than LCD as the activation energy barrier is significantly reduced by the overpotential applied at a lower voltage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several state‐of‐the‐art catalytic systems have approached similar HCD performance (including credible but not printed results as compiled in Figure S18, Supporting Information). The strategies of Pt‐ionomer relative distribution tuning with carbon support modification [ 43,68,69 ] and agglomerate engineering [ 70 ] have shown promises in enhancing both LCD and HCD performance. Catalytic activity is less relevant to HCD than LCD as the activation energy barrier is significantly reduced by the overpotential applied at a lower voltage.…”
Section: Resultsmentioning
confidence: 99%
“…Estimates made according to H 2 –O 2 data are plotted in diamonds for the grain boundary porous platinum (GBP‐Pt @0.2 mg cm −2 ), [ 67 ] Pt‐alloy/Pt‐free dual‐catalysts (LP@PF‐2@0.035 mg cm −2 ), [ 31 ] and Pt on nitrogen‐modified Ketjenblack (Pt/N‐KB @0.11 mg cm −2 ). [ 43 ] Reported H 2 –air data and estimates according to reported H 2 –air data are plotted in circles for PtCo/C nanofiber (@0.1 mg cm −2 ), [ 70 ] PtCo on HSC‐e support (@0.06 mg cm −2 ), [ 69 ] Pt/Ketjenblack by polyol reduction (Pt/KB‐PO) (@0.06 mg cm −2 ), [ 68 ] and hard magnet core–shell L1 0 ‐CoPt/Pt (@0.1 mg cm −2 ). [ 6 ]…”
Section: Resultsmentioning
confidence: 99%
“…They compared electrospun nanofiber cathodes with Nafion/PVDF and Nafion/poly(acrylic acid) (PAA) binders with a slurry cathode with neat Nafion and Nafion/PVDF binder and found that the presence of the hydrophobic PVDF reduced carbon loss and increased the binder strength [ 181 ]. In an earlier investigation, the group studied PtCo/C and Pt/C catalyst powders integrated in electrospun nanofibrous mats in comparison with conventional sprayed cathode membranes, again using Nafion/PAA as a binder, and found a higher initial performance as well as a superior long-term stability for the electrospun cathodes [ 182 ]. Similarly, Khandavalli et al used PAA to reduce agglomerations of platinum on carbon catalyst particles in catalyst inks [ 183 ].…”
Section: Fuel Cellsmentioning
confidence: 99%
“…0.2 mg Pt cm À2 , making PEMFCs approach the edge of commercial viability. [5][6][7][8][9][10][11][12] However, there is still a visible gap between the current status quo and the target. Taking both the cost to the consumer and the supply-demand relation in the precious metal market into account, a stretch target of 0.0625 g PGM kW À1 has been proposed for automobile PEMFCs.…”
Section: Introductionmentioning
confidence: 99%